2020
DOI: 10.2147/ott.s265847
|View full text |Cite
|
Sign up to set email alerts
|

<p>Curcumin Negatively Regulates Cigarette Smoke-Induced Renal Cell Carcinoma Epithelial–Mesenchymal Transition Through the ERK5/AP-1 Pathway</p>

Abstract: Background: So far, little research has been conducted regarding the underlying mechanism of renal carcinogenesis at molecular level. Epithelial-mesenchymal transition (EMT) exerts an important part during tumor genesis as well as the development through mitogen-activated protein kinase (MAPK) pathways. Therefore, we hypothesized that EMT could promote renal cell carcinoma (RCC) progression via the ERK5/AP-1pathway. Materials and Methods: The RCC cell lines were utilized to be the models with in vitro exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…These observations indicated that curcumin inhibited EMT by upregulating miR-301a-3p expression. It has been reported that curcumin suppressed EMT through the miR-200c/EPM5 axis and the ERK5/AP-1 and TET1-NKD-Wnt signaling pathways (60)(61)(62). Furthermore, our results indicated that the targeting of STAT3 by miR-301a-3p and the overexpression of STAT3 also reversed the inhibitory effects of curcumin on EMT in TPC-1 cells.…”
Section: Discussionsupporting
confidence: 66%
“…These observations indicated that curcumin inhibited EMT by upregulating miR-301a-3p expression. It has been reported that curcumin suppressed EMT through the miR-200c/EPM5 axis and the ERK5/AP-1 and TET1-NKD-Wnt signaling pathways (60)(61)(62). Furthermore, our results indicated that the targeting of STAT3 by miR-301a-3p and the overexpression of STAT3 also reversed the inhibitory effects of curcumin on EMT in TPC-1 cells.…”
Section: Discussionsupporting
confidence: 66%
“…Proofs have revealed that EMT participates in facilitating cancer aggression and migration [37]. The effects of CS on EMT and tumor developmental process have been discussed previously [7,8,[10][11][12][13][14][24][25][26][27][28][29][30]. As aforementioned, CSE elicited EMT in UMUC3 cells, as indicated by the morphologic alteration from epitheliums to mesenchyme cells.…”
Section: Discussionmentioning
confidence: 97%
“…Liang and colleagues found that curcumin reversed chronic tobacco smoke-triggered EMT in SV-HUC-1 cells and murine bladders [24,25]. Alike outcomes were found in mankind pulmonary carcinoma lineage cells ( H1299 and A549) [26], kidney cell cancer lineage cells (786-O and ACHN) [27], mouse lungs [28], mouse livers [29], and mouse stomach tissues [30]. It was reported that to evade chemoresistance, curcumin suppressed EMT and enhanced the antiproliferative capacity of conventional chemotherapeutics [23].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with synthetic drugs, treatment with natural products have fewer side effects, while exhibiting favorable outcomes ( 13 ). Although other studies have reported that several natural products, such as Epigallocatechin Gallate ( 19 ), quercetin ( 20 ), englerin A ( 21 ), honokiol ( 22 ), curcumin ( 23 ) and resveratrol ( 24 ) have shown beneficial results in preclinical studies of RCC, the research on the mechanism of the therapeutic activities of natural products on RCC is remains limited. The present study examined the antitumor effects of natural products on RCC.…”
Section: Discussionmentioning
confidence: 99%